MOTIVATION ASPECTS IN FOREIGN LANGUAGES’ ACQUISITION - Opincāne, Mārīte; Laganovska, Karīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Although foreign languages are broadly used in all spheres of life nowadays, not all students know foreign languages well.  The study of students’ needs in the personal realm results in a discussion of motivation, which is a very topical issue for teachers. Empirical, quantitative and information processing methods were used in the research process. The questionnaire was worked out and the data was analysed. The aim of the pilot research is to find out the students’ motivation to acquire foreign languages. Several conclusions and implications were worked out. Students’ attitude to the foreign languages’ acquisition is positive in general. Students would like to acquire a very broad range of foreign languages, but the offer of the schools is rather limited. The role of the teacher is to encourage students’ interest and motivate them to acquire foreign languages.